Sistem Informasi Akuntansi Media Mandar Malaqbiq - Muhammad Assiddiq (JURNAL ILMU KOMPUTER, 2016)
The volume of work which is constantly increasing demands huge resources it is intended to support the work that is effective, efficient and sustainable. Media Mandar Malaqbiq as an media print institution that manages a variety of activities with costumers who must face many obstacles in completing activities that are effective and efficient. Advances in technology are increasing can be used as a solution to this problem. This study will offer the use of information technology in the form of system that can support the process of accounting, financial transaction data processing, journaling, processing ledger, worksheet, and balance. The system is expected to help ease the tasks of employees who process a variety of data.